Evaluating dopamine transporter imaging as an enrichment biomarker in a phase 2 Parkinson’s disease trial - Hutchison, R. Matthew; Evans, Karleyton C.; Fox, Tara; Yang, Minhua; Barakos, Jerome; Bedell, Barry J.; Cedarbaum, Jesse M.; Brys, Miroslaw; Siderowf, Andrew; Lang, Anthony E. (BMC neurology, 2021)
Background Dopamine transporter single-photon emission computed tomography (DaT-SPECT) can quantify the functional integrity of the dopaminergic nerve terminals and has been suggested as an imaging modality to verify the clinical diagnosis of Parkinson's disease (PD). Depending on the stage of progression, approximately 5-15% of participants clinically diagnosed with idiopathic PD have been observed in previous studies to have normal DaT-SPECT patterns. However, the utility of DaT-SPECT in enhancing early PD participant selection in a global, multicenter clinical trial of a potentially disease-modifying therapy is not well understood. Methods The SPARK clinical trial was a phase 2 trial of cinpanemab, a monoclonal antibody against alpha-synuclein, in participants with early PD. DaT-SPECT was performed at screening to select participants with DaT-SPECT patterns consistent with degenerative parkinsonism. Acquisition was harmonised across 82 sites. Images were reconstructed and qualitatively read at a central laboratory by blinded neuroradiologists for inclusion prior to automated quantitative analysis. Results In total, 482 unique participants were screened between January 2018 and May 2019; 3.8% (15/398) of imaged participants were excluded owing to negative DaT-SPECT findings (i.e., scans without evidence of dopaminergic deficit [SWEDD]). Conclusion A smaller proportion of SPARK participants were excluded owing to SWEDD status upon DaT-SPECT screening than has been reported in prior studies. Further research is needed to understand the reasons for the low SWEDD rate in this study and whether these results are generalisable to future studies. If supported, the radiation risks, imaging costs, and operational burden of DaT-SPECT for enrichment may be mitigated by clinical assessment and other study design aspects. Trial registration ClinicalTrials.gov identifier: NCT03318523. Date submitted: October 19, 2017. First Posted: October 24, 2017. Keywords: Biomarker, Dopamine transporter, Parkinson's disease, SPECT, SWEDD